Evaluation of testicular development and morphometrics measurements in Colombian hair sheep - Espitia-Pacheco, Amado (2018)
The sheep body measurements are useful indicators of type and function that allow improving the selection. Biometric studies have shown in sheep a relationship between these measures with some productive variables. The main purpose of this study was to evaluate the testicular development and their relationship with morphometric parameters on Colombian hairy sheep of Sampués, Sucre, Colombia. Weaned males (n=12) born between February and April of 2014 were used, and the following measures were taken every twenty-eight days: scrotal circumference (CS), body weight (PC), rump height (AG), withers height (AC), and right and left testicular length (LTD and LTL).The sheep were between three to twelve months old. A multiple regression analysis (RA) was done from PC; AG; AC; TL. To describe the variation of LT, the model included only the variables PC; AG; AC. The grade of association between the studied variables was performed by a Pearson correlation. Scrotal circumference showed a high correlation with the evaluated morphometric parameters. In the RA analysis, the PC influenced the variable CE (p<0.05), while other variables did not have a significant influence. According to the regression coefficient associated to the measurement, per each kg of PC that an animal gained in weight, there was a corresponding increase of 0,09 cm in the CS.